Eficiência da alocação de encargos didáticos: uma análise dos departamentos da Universidade Federal de Santa Maria - Stefanello, Marcelo Ambrosio (2023)
Teaching load is an important input and one of the most discussed subjects in higher education institutions (HEIs), including the Federal University of Santa Maria (UFSM). In view of this, this research quantitatively studies the efficiency of the allocation of teaching load of UFSM Departments in the period from 2017 to 2021, specifically aiming to: 1) identify the Departments’ profile in relation to the resources used and results obtained to teaching load allocation; 2) estimate the efficiency of Departments and point out goals and benchmarks to those that are not efficient; and 3) verify changes in the efficiency of Departments along the time. For this, Data Envelopment Analysis (DEA) with variable returns to scale and product-oriented and the Malmquist Index was applied, operationalized by R language. 87 DMUs (86 Departments and the Academic Coordination of Cachoeira do Sul Campus) were highlighted, grouped into two clusters (C1-typical and C2- postgraduate emphasis). The analysis covered ten academic semesters (2017-1 to 2021-2) and ten variables, being one input (total teaching load per Department) and nine outputs (demands attended by the Departments). Considering the most recent semester analyzed (2021-2), 58 DMUs (66.67%) were efficient and 29 (33.33%) were non-efficient. The Department of Public Health (04.75) and the Department of Biochemistry and Molecular Biology (02.71) were the most efficient in their clusters (C1 and C2, respectively), while the Department of Performing Arts (08.40) and the Department of Social Sciences ( 06.55) were the least efficient (C1 and C2). Interestingly, no DMU showed an increasing return to scale, which means that there is no Department at UFSM that should increase its scale of operation. It was also found that 26 DMUs were consistently efficient in all semesters, and four in none. There was no occurrence of serious non-efficiency and only four occurrences of moderate non-efficiency in the ten semesters analyzed, appointing for balance and stability in the efficiency of UFSM Departments when allocating teaching load. The Malmquist Index highlighted the impact of the COVID-19 Pandemic on the productivity of DMUs that operate in a manner considered typical, with an emphasis on graduation (cluster C1), which in the first semester under the Pandemic (2020-1) there was a general reduction in productivity, influenced due to changes in the technical efficiency of DMUs (lower student participation), and in the following semester (2020-2) there was a general increase in productivity, influenced by technological changes (implementation of REDE regime). This phenomenon was not identified in the DMUs that work more actively at postgraduate level (cluster C2). Finally, as a resulting technological product, from the collected data a technical-scientific database was systematized and published.